Modifying the Health Star Rating nutrient profiling algorithm to account for ultra‐processing. - Barrett, Eden M.; Pettigrew, Simone; Neal, Bruce; Rayner, Mike; Coyle, Daisy H.; Jones, Alexandra; Maganja, Damian; Gaines, Allison; Mozaffarian, Dariush; Taylor, Fraser; Ghammachi, Nadine; Wu, Jason H. Y. (Nutrition & Dietetics, 2025)
Aim: To modify the Australian and New Zealand Health Star Rating to account for ultra‐processing and compare the alignment of the modified ratings with NOVA classifications and the current Australian Dietary Guidelines classifications of core (recommended foods) and discretionary (foods to limit). Methods: Data was cross‐sectionally analysed for 25 486 products. Four approaches were compared to the original Health Star Rating: (1) five 'negative' points added to ultra‐processed products (modification 1; inclusion approach); (2) ultra‐processed products restricted to a maximum of 3.0 Health Stars (modification 2; capping approach); (3 and 4) same approach used for modifications 1 and 2 but only applied to products that already exceeded 10 'negative' points from existing Health Star Rating attributes (modifications 3 and 4, respectively; hybrid approaches). Alignment occurred when products (i) received <3.5 Health Stars and were NOVA group 4 (for NOVA comparison) or discretionary (for Dietary Guidelines comparison), or (ii) received ≥3.5 Health Stars and were NOVA groups 1–3 or core. Results: All Health Star Rating modifications resulted in greater alignment with NOVA (ranging from 69% to 88%) compared to the original Health Star Rating (66%). None of the modifications resulted in greater alignment to the Dietary Guidelines classifications overall (69% to 76%, compared with 77% for the original Health Star Rating), but alignment varied considerably by food category. Conclusions: If ultra‐processing were incorporated into the Australian and New Zealand Health Star Rating, consideration of ultra‐processing within the broader dietary guidance framework would be essential to ensure coherent dietary messaging to Australians.